Empress San Francisco : The Pacific Rim, the Great West, and California at the Panama-Pacific International Exposition - Markwyn, Abigail M. (Book collections on Project MUSE., 2014)
When the more than 18 million visitors poured into the Panama-Pacific International Exposition (PPIE) in San Francisco in 1915, they encountered a vision of the world born out of San Francisco's particular local political and social climate. By seeking to please various constituent groups ranging from the government of Japan to local labor unions and neighborhood associations, fair organizers generated heated debate and conflict about who and what represented San Francisco, California, and the United States at the world's fair. The PPIE encapsulated the social and political tensions and confli.